Non-specific cross-reacting antigen (NCA) in individual maturation stages of myelocytic cell series. - Noworolska, A. (Nature Publishing Group, 1985)
The distribution and localization of NCA and carcinoembryonic antigen CEA in cells of different types of myelogenous leukaemias (acute myelogenous leukaemia - AML; chronic granulocytic leukaemia - CGL; CGL in myeloblastic crisis - CGL-BC) was studied using the immunofluorescence test. Discontinuous density-gradient centrifugation was used to separate myeloid cells into fractions containing granulocytes in individual stages of maturation. Serum NCA and CEA levels were estimated in parallel. It was established that: (a) AML blasts without maturation (MO type) and monoblasts did not synthesize NCA; (b) individual blasts of AML with features of maturation (M1, M2 types) and some myeloblasts of CGL-BC exhibited a limited ability to express cytoplasmic NCA; (c) the number of NCA-containing cells increased in the more mature granulocyte fractions isolated on Ficoll-Hypaque density-gradients; (d) myelocytic NCA is immunologically related to NCA isolated from lung tissue and (e) CEA is undetectable in the myelocytic cell series. IMAGES: